(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2017)
يعد القرض العام من مصادر الإيرادات العامة للدولة التي ينتفي بصددها صفة الدورية والانتظام. وتلجأ الدولة إلى هذه الوسيلة عادة ً في حالتين أساسيتين: الحالة الأولى: عندما تصل الضرائب إلى الحجم الأمثل، أي أن الطاقة الضريبية قد استنفدت، بحيث لا يجوز للدولة أن تفرض المزيد من الضرائب، وإلا ترتبت على ذلك آثار اقتصادية بالغة الخطورة. الحالة الثانية: حالة عدم وصول الضرائب إلى الحجم الأمثل، ولكن فرض المزيد منها سيؤدي إلى ردود فعل عنيفة لدى المكلفين بها. وعلى ذلك يشكل القرض العام وسيلة فعالة في يد الدولة لتجميع المدخرات التي لا تستطيع الضريبة الحصول عليها، فضلاً عن أنه أداة مهمة لتوزيع العبء المالي بين المقرضين والمكلفين. لقد أثار القرض العام خلافاً واسعاً حول طبيعته، وطبيعة العبء الذي يخلقه، ومدى ملاءمة الالتجاء إليه، وأثره في تكوين رأس المال القومي، الخ... لهذا سوف نبحث هذه المسائل وفق خطة بحث ملاءمة. هدف البحث إلى بيان ماهية القرض العام وخصائصه، وشرح مبررات اللجوء إليه، وبيان طبيعته، واستعراض آثاره الاقتصادية، وصولاً إلى نتائج البحث. The public loan is one source of the state’s public revenues, and it does not happen regularly. The state usually resorts to this source in two cases: The first case: When taxes reach the maximum degree, in other words, the taxation power is exhausted. In this situation, the state is not allowed to impose more taxes otherwise this will lead to dangerous economic effects. The second case: When taxes do not reach the maximum degree, but imposing them can lead to violent reaction by taxpayers. Therefore, the public loan constitutes an effective method in the hands of the state to collect the savings that the taxes cannot obtain. Also, it is an important tool for the distribution of the financial burden between the loaners/ and taxpayers/. The public loan has raised a controversy about its nature, the burden it causes, and its appropriateness, and its impact/role in forming the national capital, etc… Thus, these issues will be discussed in accordance with an appropriate search plan.